The Impact of Enterprise Risk Management and Sustainability Reporting on Business Performance of Listed Enterprises on Vietnam Stock Market - Anh, Nguyen Thuy; Hoa, Tran Phuong (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2021)
Enterprise Risk Management (ERM) is becoming a critical issue in the current dynamic environment where organizations have been exposed to more risks from different perspectives. Additionally, Sustainability Reporting also emerges as one of the burning topics in recent management literature. This paper examines whether ERM implementation and Sustainability Reporting could bring any effect on the business performance of Vietnamese listed companies. The paper constructs the index to measure the level of ERM implementation of listed firms in Vietnam and uses the generalized least square method (GLS) to analyze the impact of these two concerns on business performance.  The regression results indicate that there are significant positive relationships between ERM as well as Sustainability Reporting and the business performance of listed companies on the Vietnam stock exchange over the period 2016-2019. The result strengthens the previous studies that companies with more sustainability disclosure and more efficient ERM implementation are likely to be better in terms of financial performance and market performance.  Moreover, there is growing support for the argument that companies will improve their performance by employing the ERM concept and enhancing sustainability transparency to stakeholders.